Tourmaline 40Ar/39Ar geochronology and thermochronology: Example from Hadean-zircon-bearing siliciclastic metasedimentary rocks from the Yilgarn Craton. (15th May 2020) - Thern, Eric R.; Blereau, Eleanore; Jourdan, Fred; Nelson, David R.
Abstract: We present 40 Ar/ 39 Ar ages and boron isotopes of tourmalines from a quartz-tourmaline intrusion cross-cutting the Hadean detrital-zircon-bearing metasedimentary rocks from the Mt. Alfred and Brooking Hills localities of the Illaara Greenstone Belt, Western Australia. Concordant 40 Ar/ 39 Ar plateau ages on the tourmalines at Mt. Alfred give a weighted mean age of 2935 ± 9 Ma (2σ). These results are the first reported Archean 40 Ar/ 39 Ar ages directly obtained on tourmaline, and provide a minimum depositional age for this sequence, placing constraints on the depositional timing of detrital Hadean zircons to between 2935 ± 9 Ma and c.a. 3250 Ma (youngest detrital zircon age in sequence). This is the last known occurrence of abundant detrital Hadean zircons having been directly deposited in a sedimentary sequence, and thus suggests that most Hadean zircon sources have been exhausted by this time. The 2935 ± 9 Ma tourmalines occur within a quartz-tourmaline intrusion with associated stratiform layers and veins, inferred to have grown during a hydrothermal fluid circulation event. A younger generation of tourmalines from the Brooking Hills, 30 km south of Mt. Alfred yielded concordant 40 Ar/ 39 Ar plateau ages with a weighted mean age of 2624 ± 16 Ma. These tourmalines occur within and along the margins of post-kinematic quartz veins, parallel to the foliation fabric and marks the end stage of high temperature tectono-thermal events within the Illaara Greenstone Belt. The retention of 2935 ± 9 Ma tourmaline ages within the Illaara Greenstone Belt shows that the K/Ar system of tourmaline remained closed throughout repeated upper-greenschist metamorphic events (∼450 °C) between the ages of c.a. 2930 to 2630 Ma in contrast to muscovite recording plateau ages of about 2600 Ma. This is in agreement with an approximate Ar closure temperature between ∼534 and 628 °C experimentally determined in this study.